Importance Performance Analysis (IPA) of Patient Satisfaction with Fuzzy Logic at the Rumbai Maternity Clinic - Costaner, Loneli; Lisnawita, Lisnawita; Guntoro, Guntoro (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2024)
This study focuses on the level of patient satisfaction at the Rumbai Maternity Clinic. Quality of service is the main key that influences patient trust and satisfaction with this health facility. Therefore, the purpose of this study was to analyze patient satisfaction with the Importance Performance Analysis (IPA) method using fuzzy logic. This study will identify service attributes that are considered important by patients and evaluate the extent to which patient expectations have been met at the clinic. Attributes studied include cleanliness of facilities, courtesy of medical staff, availability of medicines, quality of medical services, information conveyed to patients, and others. The (IPA) method will help measure the level of importance and performance of each service attribute based on patient perceptions. Fuzzy logic is used to overcome the complexity and subjectivity of assessing patient satisfaction. The results of this study are expected to provide a comprehensive picture of patient perceptions and satisfaction at the Rumbai Maternity Clinic. Clinical management can use the results of this study to identify service improvement priorities and increase patient satisfaction. The scientific contribution of this research lies in combining the IPA method and fuzzy logic in the analysis of patient satisfaction. Thus, this research has the potential to help improve the quality of health services at the Rumbai Maternity Clinic and can be applied as a guide for developing similar methods in other health facilities.